Assessment of recent measures used to control rinderpest in Ghana - Ofosu, Samuel Achaw (The University of Edinburgh, 1978)
RINDERPEST introduced into Gold Coast (Ghana) in 1916, caused heavy losses to the cattle industry and for many years, all attention of the Animal Health Department of Ghana was directed towards the control of the disease. It was, however, only partially controlled until the institution in 1964 of the J.P-15 campaign. The J.P-15 campaign involved annual vaccination of all susceptible cattle for three consecutive years. A few difficulties were encountered but the end result was favourable. The campaign changed the status quo of the disease and now Ghana can claim to be free of rinderpest.
An assessment of recent measures used to control rinderpest in Ghana
Keywords: Annexe MSc Digitisation Project 2022 Block 40